Wound management and nursing of a patient with diabetic foot with refractory Yin syndrome (1例难治性阴证疮面脱疽患者的护理体会) - XIE Ran (谢冉); SHI Chunhong (石春红); YUE Lina (岳丽娜) (中西医结合护理)
This paper summarized the wound management and nursing of a patient with diabetic foot with refractory Yin syndrome. Patient was treated with Huiyang Shengji ointment dressing change by Traditional Chinese Medicine syndrome differentiation combined with nibbling debridement of sores, and the psychological care and health education were carried out during the treatment. The combined wound management and nursing is effective to improve the wound healing and patient’s quality of life. (本文总结1例难治性阴证疮面脱疽患者的护理体会。通过回阳生肌膏中医辨证换药结合蚕食清疮方法处理, 配合心理护理及健康宣教等, 有效促进疮面愈合, 提高患者生活质量。)